Evaluation of Nootropic activity of Cressa cretica in scopola-mine- induced memory impairment in mice - Khare, Pragati; Chaudhary, Sudhir; Singh, Lubhan; Yadav, Ghanshyam; Verma, Shashi (International Journal of Pharmacology and Toxicology, 2014)
The present investigation was undertaken to assess the pharmacological effects of Cressa cretica on learning and memory in mice. Morris water maze was used to test learning and memory. Two doses (200 and 400 mg/kg, p.o.) of ethanolic extract of Cressa cretica were administered for 28 successive days in mice. The dose of 400 mg/kg p.o. of CCE (Cressa cretica extract) significantly enhanced learning and memory of mice. This dose significantly opposed the memory loss caused by Scopolamine (0.4 mg/kg, i.p.). The effect of CCE on whole brain MDA, SOD, GSH, Catalase, NO activity was estimated to analyze how CCE shows nootropic activity. CCE reduced whole brain MDA, NO levels. Antioxidant properties and presence of flavonoids in Cressa cretica may be responsible for nootropic activity. Piracetam (200 mg/kg, i.p) was utilized as standard nootropic drug. Hence Cressa cretica seems to be a potent candidate for enhancing learning and memory and it would be beneficial for the treatment of amnesia and Alzheimer’s disease.   Keywords: Cressa Cretica, Alzheimer’s Disease (AD), Central Nervous System (CNS), Morris Water Maze (MWM), Malonyldialdehyde (MDA), Superoxide Dismutase (SOD), Nitric Oxide (NO).